(untitled) (International Journal of Engineering and Computer Science, 2017)
Modern Science has found a special place for the field of Medical Imaging and Bio-medical image processing. With the advent of advanced imaging modalities like Magnetic Resonance Imaging (MRI), Computerised Tomography (CT), Mammography, UltraSonography (USG), it is now possible to look inside into the internal structure of the ailing body. Thus, it helps to diagnose, monitor and track the abnormality, if any. This paper provides us with the results and effects of two standard thresholding techniques applied to tumor-bearing MRI images of brain. The two standard techniques implemented are the basic global thresholding method and the standard Otsu’s thresholding method. This paper studies the poor results obtained after applying these two techniques to MRI images of tumor-bearing brain and analyzes the reasons for the same.